PENGARUH SERVANT LEADERSHIP, BEBAN KERJA DAN KREATIVITAS TERHADAP KINERJA KARYAWAN DINAS PERHUBUNGAN KABUPATEN BANGKALAN MADURA DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING - Aditia Rachman Dani; Siti Mujanah (Media Mahardhika, 2021)
This research aims to, knowing the influence of servant leadership, workload, and creativity on the performance of employees of the Bangkalan Madura District Transportation Office with the organization's commitment as variable intervening. Research uses a quantitative approach. The data analysis method used is Partial Least Square (PLS). Respondents to this study were employees of bangkalan district transportation office, as many as 99 samples from the entire population of 117 employees. Data collection instruments use variable servant leadership, workload, creativity, organizational commitment and employee performance by using a Likert scale of 1-5. From the results of the analysis obtained variable servant leadership, workload, Creativity significantly influenced the commitment of the organization, while the commitment of the organization significantly affects the performance of employees. So it can be said that all hypotheses of this study are accepted. Servant leadership, creativity, work commitment and employee performance get a very good perception, but on the workload side it is expected that the leaders provide workloads in accordance with employee competence by considering the maximum limit of workload obtained by employees so that workloads do not become an obstacle in improving employee performance.